Ki Hajar Dewantara's Educational Philosophy as the Foundation of Education in the Digital Era - Bima Wisnu Gunawan; Wasilatur Rohmah (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2023)
Considering the ever-evolving digital era, this study seeks to examine the application and relevance of Ki Hajar Dewantara’s educational philosophy. Ki Hajar Dewantara, a highly influential figure in Indonesian education, held a rich and comprehensive pedagogical vision. However, it is necessary to evaluate how these conventional methods can be applied amidst the substantial challenges and transformations brought about by digital technology in the field of education. This article explores the educational principles of Ki Hajar Dewantara, including "ing ngarsa sung tulada, ing madya mangun karsa, tut wuri handayani," and their implementation in digital-era education. The findings provide valuable insight into how Ki Hajar Dewantara’s ideals and beliefs can be upheld in technology-based education.